2020
DOI: 10.3390/su12145721
|View full text |Cite
|
Sign up to set email alerts
|

Improving Energy Poverty Measurement in Southern European Regions through Equivalization of Modeled Energy Costs

Abstract: In many European countries, energy poverty is measured on the basis of real energy bills, as theoretical energy costs are hard to calculate. The UK is an exception—the data inputs for the Low Income-High Cost (LIHC) indicator are based on reasonable energy costs, these data are collected through specially designed surveys, often an intensive and costly procedure. Approaches which calculate energy needs are valid when energy bill data are unreliable or where households restrict consumption. In this analysis, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 24 publications
(59 reference statements)
0
9
0
1
Order By: Relevance
“…This risk could lead to an increased need for healthcare services, which could contribute to increasing household health expenditure burden, that is aligned with the obtained low electricity-high health expenditure situation. Furthermore, despite the warm weather, Portugal has been repeatedly considered one of the countries most affected by this issue [3,79].…”
Section: Discussionmentioning
confidence: 99%
“…This risk could lead to an increased need for healthcare services, which could contribute to increasing household health expenditure burden, that is aligned with the obtained low electricity-high health expenditure situation. Furthermore, despite the warm weather, Portugal has been repeatedly considered one of the countries most affected by this issue [3,79].…”
Section: Discussionmentioning
confidence: 99%
“…Hernández et al (2019) performed an energy audit for the building stock of Alokabide stating its good energy performance and a lower-than-expected energy consumption by the tenants. Using a different methodology, Antepara et al (2020) confirmed the observed energy under-consumption. Both studies draw a scenario similar to that described by Teli et al (2016), the fuel poverty-induced "prebound effect.…”
Section: Introductionmentioning
confidence: 55%
“…Finally, one of the limitations in the use of the ten percent rule indicator to define households' energy poverty, was derived from the relativeness among home-income levels, and the differences found between countries [85], also related to differences in national energy prices [86]. Despite being an indicator based on energy expenditure, its application in national contexts complemented with other multidimensional indicators should be considered [87], as already shown in the recent literature.…”
Section: Discussionmentioning
confidence: 99%